SISTEM INFORMASI KERJA PRAKTIK PADA DINAS PENDIDIKAN KOTA PALEMBANG MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Diki Diki; Gina Agiyani (Jurnal Riset Teknik Komputer, 2026)
The internship administration process at the Department of Education of Palembang City is is still carried out manually, including registration, document verification, activity monitoring, and report submission. This condition causes document accumulation, difficulties in data retrieval, duplication of records, and inefficiencies in monitoring internship participants. This study aims to design and develop accordingly an Internship Information System to support a more structured, efficient, and integrated administrative process. The system was developed using the Rapid Application Development (RAD) method, which consists of three main phases: requirements planning, design workshop, and implementation. Data were collected through observation, informal interviews, and literature study. The result of this research is a web-based Internship Information System that provides features such as online registration, status tracking, attendance management, task management, final report submission, grading, and certificate generation. The implementation of this system improves data management efficiency, accelerates verification processes, and enhances service quality for both administrators and students. The system also supports digital transformation efforts within the Department of Education of Palembang City.